When Risk Assessment Came to Washington: A Look Back - Joseph V. Rodricks (SAGE Publishing, 2019)
Federal regulatory agencies had, by the 1970s, been charged with enforcing a host of new laws requiring that they establish controls on human exposures to chemicals necessary to protect health. The agencies relied upon a methodology introduced in the 1950s to identify safe levels of exposure to chemicals known to display toxicity. During the 2 decades prior to the 1970s, federal authorities had come to treat carcinogens as distinct from other toxic agents, and to regard them as unsafe at any level of exposure, and no systematic methods had been developed to deal with the rapidly increasing numbers of carcinogens. Beginning in the mid-1970s, some scientists and policy makers in regulatory agencies, including the present author, began to propose adopting emerging quantitative methods to evaluate the risks of carcinogens and introduced new notions of safety based on explicit consideration of risk. Quantitative risk assessment rose to prominence in the decade reviewed in this article (1974-1984) and began to replace the unsystematic approaches that provided no view of how well health would be protected under various regulatory controls. This article offers the author's recollections of that important decade.